Cover Feature: Visible‐Light‐Induced Synthesis of 1, 2, 3, 4‐Tetrahydroquinolines through Formal [4+2] Cycloaddition of Acyclic α, β‐Unsaturated Amides and Imides with N, N‐Dialkylanilines (Chem. Eur. J. 16/2021). Issue 16 (22nd January 2021) - Itoh, Kennosuke; Nagao, Shun‐ichi; Tokunaga, Ken; Hirayama, Shigeto; Karaki, Fumika; Mizuguchi, Takaaki; Nagai, Kenichiro; Sato, Noriko; Suzuki, Mitsuaki; Hashimoto, Masashi; Fujii, Hideaki
Abstract : Inspired by Greek mythology, Orion is shown in the cover image as a lion‐hearted hunter; he hits acyclic α, β‐unsaturated imides and N, N′ ‐dialkylanilines with the club to give 1, 2, 3, 4‐tetrahydroquinolines (1, 2, 3, 4‐THQs; the lion fur in the cover image). There are three stars in Orion′s Belt; i.e., ϵ Ori, ζ Ori, and δ Ori, which enhance his toughness. The trio applied to the novel iridium(III) complex photo‐sensitizer, the thiourea, and the azo compound, works cooperatively and powerfully to achieve the photochemical synthesis of structurally diverse 1, 2, 3, 4‐THQs with excellent diastereoselectivity. More information can be found in the Full Paper by K. Itoh, H. Fujii, et al. on page 5171 .